Human Forgiveness in the Lord’s Prayer - Morgan, Robert (The expository times, 2023)
The second half of the petition for forgiveness has troubled some who think its relating divine and human forgiveness by Matthew’s ‘as’ makes the former conditional on the latter or allows human goodness to be motivated by self-interest. Luke’s alternative to Matthew’s ‘as’ may offer a way of out of this apparent dilemma if kai in the phrase kai gar at Luke 11.4b is given its ascensive meaning and the phrase translated ‘for even’, as at Luke 6.32f., and elsewhere in Luke-Acts, Paul and Hebrews.